Penerapan Project Based Learning Sebagai Upaya Meningkatkan Produktivitas Mahasiswa Saat Kuliah Daring - Yuliana Putri, Evayanti; Dwi Febriana, Linda; Ika Anggraeni, Inggrit (Jurnal Teknik Indonesia, 2022)
Introduction: Recently, online lectures have been implemented in all universities both in Indonesia and in the world as a response to the impact of the corona virus which has spread in late 2019. Online lectures are often a problem for students and teachers who have recently accessed the online system. Such conditions make students sometimes feel bored because the learning method is monotonous and the place is not conducive. Purpose: The purpose of this study is to analyzelearning innovations by implementing a Project based Learning learning system. Methods: The type of research used is quantitative by using comparative methods and questionnaire media. Data collection techniques using secondary data and sampling techniquesusing quota sampling. Results: Based on the results of the study, it was stated that students at the University of Jember felt that Project-based Learning could increase student productivity during a pandemic. A total of 47.2% of students answered productive, 25% answered very productive, 25% answered quite productive, and 2.8% answered unproductive. Conclusion: With the implementation of the Project based Learning method, all students at the University of Jember feel that Project based Learning is suitable and well applied